Incidence of Hyperlipidemia among Adults Initiating Antiretroviral Therapy in the HIV Outpatient Study (HOPS), USA, 2007–2021 - Jun Li; Selom Agbobli-Nuwoaty; Frank J. Palella; Richard M. Novak; Ellen Tedaldi; Cynthia Mayer; Jonathan D. Mahnken; Qingjiang Hou; Kimberly Carlson; Angela M. Thompson-Paul; Marcus D. Durham; Kate Buchacz (AIDS Research and Treatment)
Current U.S. guidelines recommend integrase strand transfer inhibitor (INSTI)-based antiretroviral therapy (ART) as initial treatment for people with HIV (PWH). We assessed long-term effects of INSTI use on lipid profiles in routine HIV care. We analyzed medical record data from the HIV Outpatient Study’s participants in care from 2007 to 2021. Hyperlipidemia was defined based on clinical diagnoses, treatments, and laboratory results. We calculated hyperlipidemia incidence rates and rate ratios (RRs) during initial ART and assessed predictors of incident hyperlipidemia by using Poisson regression. Among 349 eligible ART-naïve PWH, 168 were prescribed INSTI-based ART (36 raltegravir (RAL), 51 dolutegravir (DTG), and 81 INSTI-others (elvitegravir and bictegravir)) and 181 non-INSTI-based ART, including 68 protease inhibitor (PI)-based ART. During a median follow-up of 1.4 years, hyperlipidemia rates were 12.8, 22.3, 22.7, 17.4, and 12.6 per 100 person years for RAL-, DTG-, INSTI-others-, non-INSTI-PI-, and non-INSTI-non-PI-based ART, respectively. In multivariable analysis, compared with the RAL group, hyperlipidemia rates were higher in INSTI-others (RR = 2.25; 95% confidence interval (CI): 1.29–3.93) and non-INSTI-PI groups (RR = 1.89; CI: 1.12–3.19) but not statistically higher for the DTG (RR = 1.73; CI: 0.95–3.17) and non-INSTI-non-PI groups (RR = 1.55; CI: 0.92–2.62). Other factors independently associated with hyperlipidemia included older age, non-Hispanic White race/ethnicity, and ART without tenofovir disoproxil fumarate. PWH using RAL-based regimens had lower rates of incident hyperlipidemia than PWH receiving non-INSTI-PI-based ART but had similar rates as those receiving DTG-based ART, supporting federal recommendations for using DTG-based regimens as the initial therapy for ART-naïve PWH.